Analysis of patents related to microencapsulation with yam (Dioscorea Rotundata) coatings by spray drying (2021)
The objective of the work was to carry out an analysis of the patents granted and related to the process of microencapsulation of physiologically active compounds, with starchy coatings of yam (Dioscorea rotundata), by spray drying. Methodologically, a systematic process based on three stages was carried out, related to: the planning of search activities, execution and analysis of the results obtained, which led to the review of a total of 194 international patents. The result of the patent analysis allows establishing that the inventions granted related to spray drying technology were relatively low and were not directly related to the use of yams, for the development of microencapsulated products with physiologically active properties. This scenario represents multiple possibilities for the development of inventions, which involve the generation of new products with nutraceutical and pharmaceutical properties. Spray drying could also be used in inventions that contribute to the technological, operational and economic improvement of the process.